(untitled) - Cook, Diane (Hoboken, N.J., 2005)
Smart Environments contains contributions from leading researchers, describing techniques and issues related to developing and living in intelligent environments. Reflecting the multidisciplinary nature of the design of smart environments, the topics covered include the latest research in smart environment philosophical and computational architecture considerations, network protocols for smart environments, intelligent sensor networks and powerline control of devices, and action prediction and identification.
Keywords: Intelligent buildings,Telematics,Human-computer interaction,Tòa nhà thông minh,Viễn tin học,Tương tác máy tính-Con người